Neural-tuned PID controller for Point-to-point (PTP) positioning system: model reference approach - Wahyudi, Wali Ahmad; Min Htut, Myo (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.